Analisis Dampak Limbah Atau Sampah Rumah Tangga Terhadap Pencemaran Lingkungan Hidup - Mahendra, Ghazal; Salsabila, Lubna (Prosiding, 2024)
Garbage or household waste is a type of waste that originates from daily activities in the household such as plastic packaging, food waste, used bottles and cans, and other unused items, excluding feces and specific waste. If household waste cannot be managed properly it can have a negative impact on the surrounding environment. The impact of household waste also affects water quality pollution so that it will also affect health. Discarded organic waste can rot and produce methane gas which contributes to climate change. The regulation governing the environment, especially the management of household waste or waste, are regulated in PP No. 81 of 2012 concerning the Management of Household Waste and Similar Types of Household Waste. This research uses a descriptive qualitative method in which the author attempt to describe and analyze the impact of waste or household waste on environmental pollution